Synergy of Phosphate-Controlled Release and Sulfur Oxidation in Novel Polysulfide Composites for Sustainable Fertilization - Do Valle, Stella Fortuna; Giroto, Amanda Soares; Reis, Heitor Pontes Gestal [UNESP]; Guimarães, Gelton G. F.; Ribeiro, Caue (American Chemical Society (ACS), 2021)
The development of smart and eco-friendly fertilizers is pivotal to guarantee food security sustainably. Phosphate rock and struvite are promising alternatives for P fertilization; nevertheless, the solubility of these sources is a challenge for consistent use efficiency. Here, we propose using a polysulfide obtained via inverse vulcanization as a novel controlled-release fertilizer matrix in a system containing either Bayóvar rock (Bay) or struvite (Str). The polysulfide provides S for plants after being biologically oxidized to sulfate in soil, generating local acidity for P solubilization. After 15 days of soil incubation, the composites with 75 wt % Str and 75 wt % Bay achieved, respectively, 3 and 2 times the S oxidation from the elemental sulfur reference. Results indicated that P content stimulates the soil microorganisms' activity for S oxidation. The matrix had a physical role in improving Bay dissolution and regulating the rapid release from Str. Moreover, the available P in soil was 25-30 mg/dm3 for Bay composites, while for pure Bay, it was 9 mg/dm3.
Keywords: fertilizer; inverse vulcanization; phosphate; polysulfide; struvite; sulfur